2018
DOI: 10.1088/1674-1056/27/11/113201
|View full text |Cite
|
Sign up to set email alerts
|

Low-order harmonic generation of hydrogen molecular ion in laser field studied by the two-state model

Abstract: The low-order harmonic generation of hydrogen molecular ion interacting with a linearly polarized laser field has been investigated theoretically by using a simple two-state model. The validity of the two-state model is carefully examined by comparing the harmonic spectra of hydrogen molecular ion obtained from this model with those from the three-dimensional time-dependent Schrödinger equation. When combined with the Morlet transform of quantum time-frequency spectrum, the two-state model can be used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For the molecules, Avanaki et al [16] found that the 3rd, 5th, and 7th harmonics of H + 2 molecular ion were split in double peaks due to the resonance between the ground 1σ g and the first excited 1σ u states, and we [17] explain the reason due to the interference of the different cycles between the lowest two bound states of H + 2 ion by using a twostate model. [18] Therefore, the bound states have an important role on the BTHG of atom and molecule.…”
Section: Introductionmentioning
confidence: 99%
“…For the molecules, Avanaki et al [16] found that the 3rd, 5th, and 7th harmonics of H + 2 molecular ion were split in double peaks due to the resonance between the ground 1σ g and the first excited 1σ u states, and we [17] explain the reason due to the interference of the different cycles between the lowest two bound states of H + 2 ion by using a twostate model. [18] Therefore, the bound states have an important role on the BTHG of atom and molecule.…”
Section: Introductionmentioning
confidence: 99%